The mitochondrial genomes of Atlas Geckos (Quedenfeldtia): mitogenome assembly from transcriptomes and anchored hybrid enrichment datasets - Lyra, Mariana L. [UNESP]; Joger, Ulrich; Schulte, Ulrich; Slimani, Tahar; El Mouden, El Hassan; Bouazza, Abdellah; Kuenzel, Sven; Lemmon, Alan R.; Lemmon, Emily Moriarty; Vences, Miguel (Taylor & Francis Ltd, 2017)
The nearly complete mitogenomes of the two species of North African Atlas geckos, Quedenfeldtia moerens and Q. trachyblepharus were assembled from anchored hybrid enrichment data and RNAseq data. Congruent assemblies were obtained for four samples included in both datasets. We recovered the 13 protein-coding genes, 22 tRNA genes, and two rRNA genes for both species, including partial control region. The order of genes agrees with that of other geckos.
Keywords: Squamata; Gekkota; Sphaerodactylidae; Quedenfeldtia moerens; Quedenfeldtia trachyblepharus; Morocco